Pendidikan Islam Dalam Perspektif Ibnu Khaldun Dan Relevansinya Dengan Kurikulum Merdeka - Saefuddin, Muhammad Fitriadi; Nur Zam Zam, Fahmi; Kambali (Universitas Majalengka, 2024)
In this article, we will explain the deconstruction of Ibnu Khaldun's educational thought, what the concepts, goals and curriculum of education are according to Ibnu Khaldun and discuss whether this is still relevant today. The author uses the Library Research method or library method. Library research is a series of activities related to library data collection, reading, storage and processing of research materials. Ibnu Khaldun was born on 1 Ramadhan 732 H. or 27 May 1332 M. In Tunisia. His family was of Andalusian descent who emigrated to Tunisia in the mid 7 H. Ibn Khaldun's perspective on education is still in line with the independent curriculum (KM) that is implemented today. The harmony in question is found in the al-hiwar method, where in this method students will gain knowledge not only in class, through al-hiwar or direct interviews conducted with someone who is competent outside the classroom and community environment.